PENERAPAN AKUNTANSI SYARIAH PADA BUDAYA DOI PAPPENRE DI BOLAPATAPPULOE - Syulistiani (Funds: Jurnal Ilmiah Akuntansi, Keuangan, dan Bisnis, 2024)
The word doi' pappenre itself is the same as panai money, but panai money is known in the Makassar area and the word doi' pappenre is known in the Luwu, Bone Sidrap, Pinrang areas. doi' pappenre is a doi' balance from a man to his future wife because in Bugis itself women are highly valued and held in high esteem, women are often identified as crowns where not just anyone can have them or even touch them, women are a symbol of the honor and dignity of the family "tau ripu siri" therefore doi' pappenre is a form of effort by a man towards his future wife. a new view for society regarding the doi' pappenre culture which is based on the spiritual values ​​contained in the doi' pappenre culture. This research reveals the meaning or essence of doi' pappenre based on the history of doi' pappenre and will explain the factors in determining doi' pappenre. This type of research is qualitative with ethnographic techniques, namely data collection techniques, namely observation, interviews and documentation techniques. The results of the research state that the meaning of Doi pappenre in the Bugis tribal wedding tradition in Bolapatappuloe is that doi pappenre is connoted as spending money for the bride in carrying out her wedding which is solemnized by the groom. However, nowadays, the determination is based on the woman's social strata, education level and the woman's economy. In determining this, the costs involved in organizing the wedding party are also taken into account.